2012
DOI: 10.1371/journal.pone.0043764
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Metabolic Flexibility in Skeletal Muscle by a Combined Use of n-3 PUFA and Rosiglitazone in Dietary Obese Mice

Abstract: Insulin resistance, the key defect in type 2 diabetes (T2D), is associated with a low capacity to adapt fuel oxidation to fuel availability, i.e., metabolic inflexibility. This, in turn, contributes to a further damage of insulin signaling. Effectiveness of T2D treatment depends in large part on the improvement of insulin sensitivity and metabolic adaptability of the muscle, the main site of whole-body glucose utilization. We have shown previously in mice fed an obesogenic high-fat diet that a combined use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 77 publications
4
45
0
Order By: Relevance
“…Altogether, these observations suggest an improvement in the activity of β-oxidation and a better metabolic coupling between β-oxidation and the TCA cycle to overcome and limit the excess of FA. In agreement with this, metabolic explorations identified a better mitochondrial FA β-oxidation in mice fed with an imbalanced diet and supplemented with LC n-3 PUFA [60]. The modulation of the β-oxidation process by DHA could be a key element against the accumulation of reactive lipid metabolites and the related metabolic disturbances, such as IR.…”
Section: Discussionsupporting
confidence: 59%
“…Altogether, these observations suggest an improvement in the activity of β-oxidation and a better metabolic coupling between β-oxidation and the TCA cycle to overcome and limit the excess of FA. In agreement with this, metabolic explorations identified a better mitochondrial FA β-oxidation in mice fed with an imbalanced diet and supplemented with LC n-3 PUFA [60]. The modulation of the β-oxidation process by DHA could be a key element against the accumulation of reactive lipid metabolites and the related metabolic disturbances, such as IR.…”
Section: Discussionsupporting
confidence: 59%
“…The mechanisms governing the accumulation of TGs in hepatic cells include changes in hepatocellular metabolism, [23,24] propagating an imbalance between uptake and de novo fatty acid synthesis, VLDL formation and subsequent export, and oxidation capacity [25].The present study also revealed that treatment with omega-3 fatty acid showed significant reduction in the level of triglycerides and NEFA in plasma compared to those of HFD treated group. This is in agreement with the previous [26,27]which supports the triglyceride-lowering properties of omega-3 fatty acid and decreased NEFA level in plasma. This could be explained by changes in transcription of several nuclear receptors are reported to mediate the TG-reducing effects of omega-3 fatty acid: sterol regulatory element binding proteins (SREBP), liver X receptor-alpha (LXRα), retinoid X receptor alpha (RXRα), farnesoid X receptor (FXR), and peroxisome proliferator-activated receptors (PPARs), and each play prominent roles in controlling lipid metabolism.…”
Section: Discussion:-supporting
confidence: 93%
“…Thus, some studies support that n-3 PUFAs can significantly decrease body weight and fat mass [36][37][38][39][40][41][42][43][44][45][46][47]. Other trials did not find any significant action on body weight loss but a significant reduction in some fat depots was observed in n-3 PUFAs supplemented groups [45,[48][49][50].…”
Section: Evidence From Animal Modelsmentioning
confidence: 99%